Perlindungan Hak Anak Korban Kekerasan Seksual di Nusa Tenggara Barat - Penny Naluria Utami (Badan Strategi Kebijakan Hukum, 2015)
Sexual abuse of children are serious crimes that can occur in children, anywhere, anytime and regardless of their social background. Crime is mostly carried out by someone in the child's social environment, such as family, relatives, family friends, teachers, religious leaders, and neighbors. The effects of sexual assault for victims of very serious because of perceived trauma will continue to carry over until they mature and can affect all aspects of their lives and threaten the lives of children as the future generation. Many of the factors that trigger the occurrence of sexual violence against children in West Nusa Tenggara, namely poverty, education is still low and cases of early marriage. The phenomenon of early marriage is causing risk of disruption to children's education, especially for girls. This study is a qualitative research that focuses on the phenomenological paradigm that seeks to understand the meaning of the event or events that are related to the situation on the ground. This type of research is descriptive analytical approach, which wants to give a clear and detailed description as well as systematic, on all matters relating to the protection of child victims of sexual violence. Results of the study in order to become the recommendation for the central government and local government as research areas in formulating policy strategy is best for the child victims of sexual violence. There are still many cases are not reported because families consider it a disgrace and families often suggested or decided to reconcile with the perpetrator if a relative or family, so that the data presented in the case of the police or the court is only the tip of the iceberg compared to the actual events occur. Encourages all stakeholders including central and local government, police, prosecutors and judges, to have the same perception of the law on the protection of children in order to provide future better for the children of Indonesia.